Não matarás e a ampliação do olhar reflexivo : desejo e ética na obra de Kieslowski - Hokama, Humberto (Universidade Federal de São Carlos, 2015)
This project aims to investigate aesthetic and signal subjects of Kieslowskian cinematographic language from the analysis of the episode 5 of the television series Decalogue (1988) and its respective version for cinema A short film about killing (1988). The aim is to study how Kieslowski constructs new relationships in extended version of this episode, the motivations that led him to rearrange them and/or reconstruct them, and what this option by “duplicating” the same movie can tell us about the cinema conception of this Polish director.
Keywords: Análise fílmica; Krzysztof Kieslowski; Projeto poético; Duplicidade; Decálogo; A short film about killing; Decalogue; Film analysis; Creative process; Duplicity; LINGUISTICA, LETRAS E ARTES::ARTES